Food Production, Processing and Foodways in Neolithic Ireland. (2nd January 2022) - McClatchie, Meriel; Schulting, Rick; McLaughlin, Rowan; Colledge, Sue; Bogaard, Amy; Barratt, Phil; Whitehouse, Nicki
ABSTRACT: When compared with earlier periods, the Neolithic in Ireland (4000–2500 cal BC) witnessed enormous changes in the foods being produced, and the work involved in their production and processing. Several crops were introduced – archaeobotanical studies indicate that emmer wheat became the dominant crop, with evidence also for barley (hulled and naked) and flax. Gathered resources were not abandoned; on the contrary, there is substantial evidence for a variety of nuts, fruits and leafy greens. Zooarchaeological studies indicate that new animals also arrived, including domesticated cattle, pig and sheep. Recent studies have provided substantial information on the timing and nature of these new ways of farming and living, but the focus is often on ingredients rather than food products. There are many challenges in determining which foods were being made with these new crops and animals, and in assessing their dietary and social importance. While cereals have been found at many sites, for example, it is not clear if they are being ground, boiled or other techniques are used for their processing. In this paper we explore aspects of food production, processing and foodways in Neolithic Ireland, drawing upon evidence from archaeobotany, zooarchaeology, isotopes, human skeletal remains and artefacts.